Breath acetone concentration; biological variability and the influence of diet - Spaněl, Patrik; Dryahina, Kseniya; Rejšková, Alžběta; Chippendale, Thomas W E; Smith, David (Physiological measurement, 2011)
Previous measurements of acetone concentrations in the exhaled breath of healthy individuals and the small amount of comparable data for individuals suffering from diabetes are briefly reviewed as a prelude to the presentation of new data on the sporadic and wide variations of breath acetone that occur in ostensibly healthy individuals. Data are also presented which show that following a ketogenic diet taken by eight healthy individuals their breath acetone concentrations increased up to five times over the subsequent 6 h. Similarly, the breath acetone increased six and nine times when a low carbohydrate diet was taken by two volunteers and remained high for the several days for which the diet was continued. These new data, together with the previous data, clearly indicate that diet and natural intra-individual biological and diurnal variability result in wide variations in breath acetone concentration. This places an uncertainty in the use of breath acetone alone to monitor blood glucose and glycaemic control, except and unless the individual acts as their own control and is cognizant of the need for dietary control.
Keywords: Exhalation; Diet, Ketogenic; ketogenní dieta; Male; Dietary Carbohydrates; dospělí; lidé; hmotnostní spektrometrie; senioři; Aged; Acetone; vydechnutí; aceton; dechové testy; ženské pohlaví; Adult; Breath Tests; mužské pohlaví; dietní sacharidy; Humans; Mass Spectrometry; Female